NOVEL DETECTION PLATFORM FOR ALZHEIMER'S AMYLOID-BETA USING MAGNETIC BEADS IN ELECTROCHEMICAL IMPEDANCE SPECTROSCOPY - Shin, Kyeong-Sik; Kim, Moo Jong; Lee, Soo Hyun; Kang, Ji Yoon (2015 28TH IEEE INTERNATIONAL CONFERENCE ON MICRO ELECTRO MECHANICAL SYSTEMS (MEMS 2015), 2015)
In this paper, we proposed novel detection platform to detect Alzheimer's amyloid-beta (A beta) using pre-treated magnetic beads in Electrochemical Impedance Spectroscopy (EIS), for the first time. Without any immobilization on the electrodes of the EIS device, it shows ability to detect a few pg/ml of amyloid-beta oligomers and compared to the result of a conventional ELISA, which allows to simplify the measurement procedure, recycle the device by only changing magnet beads.